The dream giver - Wilkinson, Bruce; Kopp, David, 1949-; Kopp, Heather Harpham, 1964- (Sisters, Or. : Multnomah Publishers, 2003)
A modern-day parable explains how to achieve one's dreams and overcome the obstacles that stand in the way of leading the life God intended.
Keywords: Success -- Religious aspects -- Christianity